Fast response fibre bragg grating (FBG) pressure transducer - Z. M., Hafizi; Muhammad Aizzuddin, Abdullah; Vorathin, E.; Aziman, Abdullah (2018)
FBG pressure sensor has shown a great potential in replacing conventional electrical pressure sensor due to its adaptability to harsh environment. However, increasing its sensitivity is still a challenge. In this work, bonding of FBG to a rubber-based diaphragm pressure transducer was proposed and experimentally presented. The improved design of the rubber-based diaphragm has enhanced the sensitivity and sensing range recorded at 118.03 nm/MPa or 7.614 x 10-2 MPa-1 across a range of 0.08 MPa with a good linearity of 99.8%. Furthermore, the thermal-strain cross sensitivity was totally compensated.